Scheme Change Strategy in the Translation of Rhetorical Repetition in “Babbity Rabbity and Her Cackling Stump” - Adani Nur Sabrina (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study investigates the translation of rhetorical repetition devices in the tale Babbity Rabbity and Her Cackling Stump by J.K. Rowling, and its Indonesian version Babbity Rabbity dan Tunggul Terbahak, using Chesterman’s scheme change strategy. The aims of this research are to identify the types of rhetorical repetition used and to examine how they are translated from English into Indonesian. This research employs a descriptive qualitative method, with data collected from both the source and target texts. Purposeful random sampling was used to analyze representative data from each category. Thirteen instances of rhetorical repetition were found and categorized into four scheme change strategies: ST scheme X → TT scheme X, ST scheme X → TT scheme Y, ST scheme X → TT scheme Ø, and ST scheme Ø → TT scheme X. The analysis reveals that all four strategies were applied, with most data preserving the same rhetorical scheme in translation. Some examples also exhibited multi-layered repetition, combining more than one rhetorical feature such as parallelism, end rhyme, and alliteration. This study contributes to the field of literary translation by highlighting the stylistic challenges involved in translating rhetorical features, and may serve as a reference for translators or scholars interested in stylistic equivalence in translation.